Stress Adaptation as an Improvement Effort Self- Management and Quality of Life in Patients with Chronic Kidney Disease: A Literature Review - Maria, Kiki; Rondhianto, Rondhianto; Suhari, Suhari (Indonesian Journal of Global Health Research, 2024)
Chronic Kidney Disease (CKD) is a significant health issue closely associated with mortality. The prevalence of this disease has been increasing significantly worldwide each year. It is characterized by a permanent decline in kidney function that cannot be reversed within three months or even many years. Eventually, the kidneys may cease to function properly. Failure to adapt to stress impacts the mechanism of coping, self-awareness self-control, and self-efficacy decreasing that impact on self-management and quality of life. This research aims to illustrate the influence of adaptation to stress as effort enhancement self-management and quality of life in patients with chronic kidney disease. A systematic review using the PRISMA protocol and the JBI Critical Appraisal Tool was used to determine which articles met the three requirements of electronic databases (PubMed, Google Scholar, ScienceDirect ). Inclusion criteria include the quality of life of chronic kidney disease patients published in English within the last 5 years (2019-2024). This summarizes twenty - two articles. Discuss the influence of adaptation to stress, self-management, and quality of life for patients with chronic kidney disease. Self-management and quality of life in patients with chronic kidney disease are influenced by adaptive stress, including 1) Focal stimuli (level of severity, duration of hemodialysis, symptoms), 2) Contextual stimuli (distance to health facility, family support, power of health support, satisfaction with health service, employment, economic status, health insurance, marital status), 3) Residual stimuli (age, religion, level of education, sex of type). Positive coping strategies, self-awareness, self-control, and self-efficacy can improve the adaptation process to stress, thus having a positive impact on self-management and quality of life in patients with chronic kidney disease.